ANALISIS PENGARUH BEBAN KENDARAAN TERHADAP SISA UMUR RENCANA JALAN PADA RUAS JALAN SOENANDAR PRIYO SUDARMO, KABUPATEN SIDOARJO - Aldy Syahputra; Ibnu Sholichin; Aulia Dewi Fatikasari (LPPM Universitas Abdurrab, 2026)
Soenandar Priyo Sudarmo Road, located in Sidoarjo Regency, East Java, is surrounded by various industrial facilities and storage warehouses, leading to significant stress on the pavement due to heavy vehicle traffic. This condition increases the risk of pavement deterioration. Therefore, this study aims to evaluate the impact of overloaded vehicles on the remaining service life of the pavement along Soenandar Priyo Sudarmo Road. The study utilizes both secondary data—such as Average Daily Traffic (ADT) and vehicle loads—and primary data obtained through field traffic surveys. The AASHTO 1993 method is employed to analyze the effect of vehicular loads on pavement life. Two scenarios are assessed: first, assuming all vehicles comply with standard axle loads; and second, analyzing the condition with overloaded freight vehicles based on actual overload data. Calculations include ESAL, W18, truck factor, and remaining pavement life. The analysis results indicate that the cumulative standard load (ΣW18) ranges from 372,983.25 to 16,839,371.72, while the overloaded condition ranges from 731,161.54 to 31,982,312.35. The remaining life percentage under overloaded traffic is reduced by 31%, resulting in a decreased service life of 3.1 years. Consequently, the pavement is projected to reach the end of its design life by November 2028.